Rape, incest, battery : women writing out the pain - Harris, Miriam Kalman, 1942- (TCU Press, 2000)
Publisher's description: Rape, incest, and battery change a woman's life forever. Some women never rise above the pain, the rage, the humiliation, while others seem to transcend the violence and rebuild their lives. What distinguishes those who transcend the violation? Courage--the courage to face their past and, sometimes, to put it into words. In 1989 Miriam Harris was serving as project coordinator for the Battered Woman's Emergency Intervention Project at Dallas's Parkland Hospital. As part of her duties, she taught a journal-writing class at a women's shelter and found that the women she helped to express their pain, rage, and frustration underwent a catharsis of the soul, but, more importantly, understood the heroic enterprise of regaining self-power. "The writing cure," as she calls it, builds on the "talking cure" that originated with Sigmund Freud's famous patient, Anna O. According to Harris, a woman discovers a new identity by becoming the "subject who writes" rather than the victim who waits in silence. Knowing that the problem of violence against women is universal in our world, Harris put out a call to professional writers, women in shelters, and scholars in academe. She advertised in literary journals and newsletters, asking for autobiographical writings by women who survived any kind of violence and abuse. Rape, Incest, Battery resulted from her long process of collecting, selecting, and editing. Divided into seven sections, this anthology is arranged in the pattern a journey might take: "Silent Woman Speaks" redefines the events of the past; "Thoughts after Rape" explores the continuum of sexual violence in our culture; "Dark Pages" lights the dark of childhood, too often revealing abuse and incest; "Grinding Axes" calls attention to the price women pay for accepting society's definitions of gender; "Behind His Walls" explores imprisonment, both actual and metaphorical; "Regeneration" captures the moment of rebirth; and "She Said NO!" affirms female strength. A woman is raped every three minutes; a woman is beaten in her home every fifteen seconds; one of four women in emergency rooms is "battered." Over four million women are beaten annually by current and former male partners, and between two thousand and four thousand are murdered. But this book goes beyond the overwhelming magnitude of the problem to celebrate the images of heroic women fighting for their rights, risking their lives, rescuing their children from a violent family life, testifying, speaking out, and seeking justice when they are beaten, raped, or otherwise violated